Numerical blood flow simulation with predefined artery movement - Piskin, Senol; Celebi, M. Serdar (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In this study, the blood flow in human arteries is modelled. Three dimensional artery geometry is used as the model domain. The geometric model is generated using several parameters of arteries such as radius, length and curvature. After the geometry is determined, blood flow and wall movement models are constructed. For blood flow, Navier-Stokes equations are solved under the assumptions of Newtonian, incompressible flow and constant viscosity. For artery movement, elastic, homogeneous and isotropic material assumptions are implemented. Blood flow and artery movement models are coupled and solved together. The average pressure value acquired from flow model is set as the loading condition of artery movement. The displacement of artery is used to produce new geometry of flow model for the next time step. At the entrance of the artery, Womersley velocity profile is used. This profile is generated using the flow rate data obtained by experimental studies. Thus, the mechanical properties of blood flow such as velocity profiles, wall shear stress and pressure distribution in arteries are investigated. Initial results reveal that that blood flow - artery wall movement coupling model allows to relate the development of vortices, low wall shear stress zones and others to the cardiovascular diseases.